Emotion categorization and early bilinguals : a study of Chinese-English bilinguals’ understanding of the shame category - Lin, Bai (2015)
Past studies show that different cultures/languages socialize speakers into different manners of interpreting and categorizing emotional experiences (Wierzbicka, 1986; 1999). The present thesis investigates how emotions are categorized for bilinguals who have access to two distinct language systems with culture- and language-specific features. Do bilinguals maintain two sets of categorization systems, or do they have one system that incorporates features of both languages? To date, not many studies have empirically examined how bilinguals categorize emotional experiences, and the majority of studies on emotions examine late or sequential bilinguals rather than early bilinguals. As an attempt to bridge the above research gap, this dissertation examines how Chinese-English early bilinguals understand shame, as shame is categorized very differently in Chinese and English (e.g., Li, Wang & Fischer, 2004; Shaver, Wu & Schwartz, 1992). The measurement used included a free listing task, a similarity sorting task, and a semantic profile questionnaire, as well as an individualism and collectivism questionnaire. The results show that early bilinguals’ two categorization systems mutually influence each other, leading to commonalities in three dimensions: the prototypical shame expressions, the semantic structures formed by the prototypical shame expressions, and the semantic features associated with these central shame expressions. Moreover, the results provide empirical evidence that bilinguals’ shame categorization is an ongoing dynamic process influenced by their language preference (for expressing emotions), language dominance, and culture orientations. First, bilingual participants list more prototypical shame members in their preferred language. Second, bilingual participants who prefer Mandarin Chinese have more elaborate semantic structures for shame in both languages, while those who prefer English have simpler semantic structures in both languages. Third, bilingual participants’ semantic understanding of central shame terms is also shaped by their language dominance and culture orientation. For those who are dominant in Chinese, it is more likely for them to consider it socially acceptable to express shame in public, and less likely for them to use shame words to refer to intense experiences. In contrast, the more English-dominant they are, the more likely it is for them to associate shame experiences with inferiority or worthlessness. Regardless of language dominance, the more individualist-oriented the bilingual participants are, the less likely it is for them to consider it socially appropriate to express shame in public, and the more likely for them to use shame words for intense experiences. The more collectivist-oriented they are, the more likely it is for them to use shame words for experiences that have an impact on others. Taken together, the present series of experiments represents an attempt to illustrate the impact of early bilingualism on the categorization of emotion.